2020
DOI: 10.1371/journal.pone.0230151
|View full text |Cite|
|
Sign up to set email alerts
|

Phylogeny of the Eurasian Wren Nannus troglodytes (Aves: Passeriformes: Troglodytidae) reveals deep and complex diversification patterns of Ibero-Maghrebian and Cyrenaican populations

Abstract: The Mediterranean Basin represents a Global Biodiversity Hotspot where many organisms show high inter-and intraspecific differentiation. Extant phylogeographic patterns of terrestrial circum-Mediterranean faunas were mainly shaped through Pleistocene range shifts and range fragmentations due to retreat into different glacial refugia. Thus, several extant Mediterranean bird species have diversified by surviving glaciations in different hospitable refugia and subsequently expanded their distribution ranges durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 148 publications
(199 reference statements)
0
6
0
Order By: Relevance
“…A previous study based on mitochondrial CO1 sequences also reported a high level of sequence divergence between a single bird from the Caucasus (Krasnodar, Russia) and six individuals from elsewhere in Russia (Kerr et al, 2009; see also Bilgin et al, 2016). Genetic distinctiveness of Caucasian populations was already documented for other Palearctic species, such as the Eurasian Nuthatch, Sitta europaea (Nazarizadeh et al, 2016; Päckert et al, 2020), the Coal Tit, Periparus ater (Tietze et al, 2011), the Dunnock, Prunella modularis (Drovetski et al, 2018) and the Eurasian Wren, Troglodytes troglodytes (Albrecht et al, 2020). Morphologically, E. r. caucasicus differs from European E. rubecula by its rufous uppertail‐coverts and basal half of the tail (Roselaar in Cramp, 1988).…”
Section: Discussionmentioning
confidence: 85%
“…A previous study based on mitochondrial CO1 sequences also reported a high level of sequence divergence between a single bird from the Caucasus (Krasnodar, Russia) and six individuals from elsewhere in Russia (Kerr et al, 2009; see also Bilgin et al, 2016). Genetic distinctiveness of Caucasian populations was already documented for other Palearctic species, such as the Eurasian Nuthatch, Sitta europaea (Nazarizadeh et al, 2016; Päckert et al, 2020), the Coal Tit, Periparus ater (Tietze et al, 2011), the Dunnock, Prunella modularis (Drovetski et al, 2018) and the Eurasian Wren, Troglodytes troglodytes (Albrecht et al, 2020). Morphologically, E. r. caucasicus differs from European E. rubecula by its rufous uppertail‐coverts and basal half of the tail (Roselaar in Cramp, 1988).…”
Section: Discussionmentioning
confidence: 85%
“…The second challenge is particularly important in relation to the southern areas of Europe, several of which are known glacial refugia. It is clear that these refugia played a decisive role in shaping intra and interspecific geographical variations, with phylogeographic studies identifying Iberia, Southern Italy or the Balkans as regions where populations accumulated genetic differences (e.g., Brito 2005;Pellegrino et al 2015;Drovetski et al 2018a;Albrecht et al 2020). Strong intraspecific differentiation is rare in migratory WP species (Pârâu & Wink 2021), being instead largely confined to sedentary or short-distance (intra-Palearctic) species.…”
Section: Introductionmentioning
confidence: 99%
“…The second challenge is particularly important in relation to the southern areas of Europe, several of which are known glacial refugia. It is clear that these refugia played a decisive role in shaping intra and interspecific geographical variations, with phylogeographic studies identifying Iberia, Southern Italy or the Balkans as regions where populations accumulated genetic differences (e.g., Brito 2005;Pellegrino et al 2015;Drovetski et al 2018a;Albrecht et al 2020). Strong intraspecific differentiation is rare in migratory WP species (Pârâu and Wink 2021), being instead largely confined to sedentary or short-distance (intra-Palearctic) species.…”
Section: Introductionmentioning
confidence: 99%